DIAGNOSIS AND TREATMENT OF PROXIMAL HUMERUS FRACTURES - A. M. Fain; A. Y. Vaza; V. V. Slastinin; R. S. Titov (Неотложная медицинская помощь)
Proximal humeral fractures typically occur in elderly patients and lead to significant functional disorders. There are many different nonsurgical and surgical treatment options for these injuries, including immobilization and early physical therapy, percutaneous K-wires fixation, plate osteosynthesis, intramedullary nailing and shoulder arthroplasty. The choice of treatment depends on the fracture type and severity, surgeon skill level, patient’s age and health status. Today, there is no single algorithm for treating such injuries, there are no large randomized studies which allow it to be created. The aim of this article is to generalize various methods of treatment and diagnosis of fractures of the proximal humerus.